Enhancing Human Resource Performance: An Evaluation Study Using the Human Resource Scorecard Method at PT. Wanxiang Nickel Indonesia in Morowali - Fole, Asrul; Safutra, Nur Ihwan; Safitri, Khoerun Nisa; Rizki Febriani (TALENTA Publisher, 2025)
This study evaluates the performance of human resources at PT. Wanxiang Nickel Indonesia (WNI), is influenced by a lack of responsibility, low awareness of work risks, and insufficient employee skills. The research method employed is the Human Resources Scorecard (HRS), involving a Likert scale for Key Performance Indicators (KPI) and Pairwise Comparison in the Analytical Hierarchy Process (AHP). The results of the study indicate the highest weight is found in the perspective of employees' intellectual competence (1.079) and work competence (0.981), followed by emotional competence (0.303) and personality competence (0.246). This research aims to improve human resource (HR) performance and productivity within the company. The intellectual and work perspectives play a significant role in the evaluation, while emotional and personality perspectives also contribute meaningfully. Recommendations: the company needs to develop these perspectives in a balanced manner to enhance overall human resource performance and productivity at PT. WNI.